2012
DOI: 10.1007/s12035-012-8377-3
|View full text |Cite
|
Sign up to set email alerts
|

Brain Endogenous Estrogen Levels Determine Responses to Estrogen Replacement Therapy via Regulation of BACE1 and NEP in Female Alzheimer’s Transgenic Mice

Abstract: Estrogens have been found to improve memory and reduce risk of dementia, although conflicting results such as failure of estrogen replacement therapy for treatment of Alzheimer’s disease (AD) also has been reported. Only recently, our published human brain studies showed a depletion of brain estrogen in women with Alzheimer’s disease, while other studies have demonstrated cognitive impairment believed to be caused by inhibition of endogenous estrogen synthesis in females. To investigate whether the shortage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 51 publications
2
54
0
2
Order By: Relevance
“…The low estrogen concentration in APP23 mice with genetic deficiency of aromatase is characterized by a more severe formation of Aβ plaques and an extensive AD neuropathology than that found in ovaricetomized mice, suggesting that the deficiency of endogenous estrogens in the brain could increase the risk of Alzheimer’s disease. This estrogen-deficient mouse model was even more sensitive to the reduction of plaque formation by genistein than by endogenous estrogens, thus supporting the beneficial effect of this exogenous phytoestrogen [123]. An intriguing study of genistein on brains of ovariectomized rats showed that genistein mimicked the estradiol-induced effects by enhancing place learning, but it also impaired response learning compared to untreated animals.…”
Section: Update On Chemical Classes Comprising Erα and Erβ Modulatorsmentioning
confidence: 83%
“…The low estrogen concentration in APP23 mice with genetic deficiency of aromatase is characterized by a more severe formation of Aβ plaques and an extensive AD neuropathology than that found in ovaricetomized mice, suggesting that the deficiency of endogenous estrogens in the brain could increase the risk of Alzheimer’s disease. This estrogen-deficient mouse model was even more sensitive to the reduction of plaque formation by genistein than by endogenous estrogens, thus supporting the beneficial effect of this exogenous phytoestrogen [123]. An intriguing study of genistein on brains of ovariectomized rats showed that genistein mimicked the estradiol-induced effects by enhancing place learning, but it also impaired response learning compared to untreated animals.…”
Section: Update On Chemical Classes Comprising Erα and Erβ Modulatorsmentioning
confidence: 83%
“…Thus, in H19-7 hippocampal cells, the inhibition of aromatase prevents the neuroprotective action of exogenous oestradiol 126 . In addition, the neuroprotective action of circulating oestradiol in a mouse model of Alzheimer's disease is significantly reduced in ArKO mice that have undetectable levels of brain oestradiol 127 . Further studies are necessary to clarify the role of brain oestradiol synthesis in the neuroprotective outcome of hormone therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Although in vitro research demonstrated the neurotrophic and neuroprotective effects of estrogen on neurodegenerative diseases, such as AD, the data obtained from the clinical studies is conflicted [10-16]. After observing a reduction in brain estrogen in female patients with AD, estrogen/hormone replacement therapy has been utilized [12, 17-19]. Early trials supported the idea that patients with AD could benefit from estrogen therapy according to its improving effects on memory and cognitive functions; however, these studies were conducted on perimenopausal women or healthy postmenopausal women [19, 20].…”
Section: Introductionmentioning
confidence: 99%